Peningkatan Kompetensi Guru Dalam Menerapkan Pembelajaran Daring Masa Pandemi Covid 19 di UPTD SDN Sejati 1 - Sutikno Sutikno (Journal on Education, 2023)
This research aims to improve teachers' ability to apply online learning during the Covid 19 pandemic at UPTD SDN Sejati 1. This type of research is school action research (action research). The research being carried out is qualitative research, namely research that explains the efforts made to improve teachers' abilities in carrying out online learning in the teaching and learning process. This research was carried out at UPTD SDN Sejati 1, Sampang District, 2019/2020 Academic Year. The subjects in this study were all teachers at UPTD SDN Sejati 1, totaling 16 teachers. Based on observations, these teachers were not optimal in implementing online learning. The object of this research is an effort to improve teachers' abilities in online learning through the Google Classroom application. The research instrument is in the form of a questionnaire sheet, which is useful for recording all events of carrying out teacher assignments in online learning during research. The results of the research show that the understanding of teachers at UPTD SDN Sejati 1 in online learning is in accordance with the demands of the Government during the Covid-19 Pandemic which required teachers to carry out online learning that has been implemented and carried out properly at UPTD SDN Sejati 1. The results show that In Cycle I, the teacher's understanding of online learning was carried out during the learning process at UPTD SDN Sejati 1, the number of which was 1,260. The average value is 37, with a percentage of 77.20%. Thus the understanding of teachers at UPTD SDN Sejati 1 is in the Fairly Good category. Then it increased after the implementation of Cycle II of Online Learning which was carried out during the learning process at UPTD SDN Sejati 1, the number was 1,339. The average value is 39, with a percentage of 82.04%. Thus the understanding of teachers at UPTD SDN Sejati 1 is in the Good category. The results of the study show that the teacher's understanding of online learning at UPTD SDN Sejati 1 is in the good category